2004
DOI: 10.1111/j.1523-1755.2004.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil in IgA nephropathy: Results of a 3-year prospective placebo-controlled randomized study

Abstract: In patients with IgAN at risk for progressive disease, no beneficial effect of 3-year treatment with MMF 2 g per day could be demonstrated on renal function/outcome or proteinuria. However, larger randomized studies are needed to confirm or reject these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
159
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(165 citation statements)
references
References 28 publications
2
159
2
2
Order By: Relevance
“…However in this study BP control was well above currently accepted goals, and the use of RAS blockade was not reported [4]. Other recent RCTs of immune modulating therapy have used supportive therapy as 'standard of care' including three small studies of mycophenolate; among these trials, one, conducted in a Chinese population, indicated benefit [10] while two others, both in European populations, did not [11,12].…”
Section: What Does This Important Study Show?mentioning
confidence: 73%
“…However in this study BP control was well above currently accepted goals, and the use of RAS blockade was not reported [4]. Other recent RCTs of immune modulating therapy have used supportive therapy as 'standard of care' including three small studies of mycophenolate; among these trials, one, conducted in a Chinese population, indicated benefit [10] while two others, both in European populations, did not [11,12].…”
Section: What Does This Important Study Show?mentioning
confidence: 73%
“…To date only four RCTs have compared MMF with placebo [4][5][6][7]11] and results have been conflicting. All studies have been small (between 17 and 22 patients receiving MMF monotherapy) and have utilised different inclusion criteria, ethnic populations and durations of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…All studies have been small (between 17 and 22 patients receiving MMF monotherapy) and have utilised different inclusion criteria, ethnic populations and durations of follow up. Early studies from Belgium [4] and North America [5,7] showed no benefit from MMF therapy in treating IgAN. In contrast, Tang and colleagues found MMF significantly increased the likelihood of remission from proteinuria in a cohort of Chinese patients and lowered the risk of progression to end stage kidney disease compared to RAAS alone [6,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations